Synthesis of (La + Nb) co-doped TiO2 rutile nanoparticles and dielectric properties of their derived ceramics composed of submicron-sized grains. Issue 7 (1st April 2021) - Li, Jingxuan; Zeng, Yu; Fang, Yihang; Chen, Nan; Du, Guoping; Zhang, Aisheng
Abstract: In this work, a sol-gel method was used to synthesize nanometer-sized rutile (La + Nb) co-doped TiO2 powders, which were employed to prepare (La + Nb) co-doped TiO2 ceramics. The average grain size of the (La + Nb) co-doped TiO2 ceramics was less than 200 nm, which is much smaller than that of conventionally prepared co-doped TiO2 ceramics generally having micron-sized grains. The effect of the (La + Nb) co-doping concentration on the microstructures and dielectric properties of the obtained ceramics was studied in detail. For a 2% co-doping concentration, it was found that the (La + Nb) co-doped TiO2 ceramic had dielectric permittivity (εʹ) higher than 2 × 10 4 for frequency up to 1 MHz and the lowest dielectric loss (tanδ) was 0.019 at 1 kHz. The electron hopping and electron-pinned defect-dipole effect was considered as the main reasons for colossal permittivity and low tanδ. This work provides a technique for the synthesis of co-doped TiO2 nanoparticles and preparation of submicron-grain-sized co-doped TiO2 ceramics with good dielectric properties.